Effects of advisory services on growth of small scale food manufacturers in Selangor, Malaysia - Ahmad, Suwardi Afandi (2013)
Small and medium-sized enterprises (SMEs) have been instrumental to the growth of Malaysia's economic development. Among the significant contribution was in terms of providing employment, increased export and national income. Realizing this fact, various initiatives have been introduced by the government in order to strengthen the SMEs development. Advisory service program is one of the initiatives established with the aim to assist and guide the SMEs particularly in the manufacturing sector. There are currently more than 60 agencies involved in providing advisory services to the SMEs. The types of advisory services given depend on the core business of the institutions but usually consist of technical and business advices. Based on statistical record, about 34,000 SMEs in various sectors had received advisory services from various government agencies. Through the provision of the advisory services, it is hoped that the capability of the SMEs will be increased. However, such expectation needs to be confirmed and supported with empirical research. Thus, the main objective of this study was to evaluate the impact of the advisory services upon the business performance of the firm. Performance will be measured by two indicators r: namely firm sales' growth and the inherent ability to manage the business. The sample size of this study was 103 food manufacturers in Selangor which received advisory services from government agencies. The primary data was gathered through face to face interview using standard questionnaires. The data was analyzed using descriptive statistics, factor analysis and logistic regression analysis. Results showed that advisory services received by the respondent had positive and significant relationship with sales while for ability to manage the business indicated positive and significant relationship only for business and management advices. This study suggests that the advisory services program is beneficial and should be continued. The findings also highlight the perception of the respondent against thirteen aspects pertaining to the service delivery system that need to be improved due to their lowest ratings. Four factors consisting of prompt action, good communication skills, current technology and better equipped facilities were identified to influence the reception of the services given. Thus, this study recommends that the advisory agencies should prioritize and integrate these four factors for the effectiveness of their advisory service programs.